Family Support With Self-Care Ability In Mental Retardation Children In SLB State 1 Bulukumba - Tenriwati; Haerani; Rahmi Islamiah (Comprehensive Health Care, 2018)
Mental retardation is a lack of intelligence. Children with mental retardation in addition to having limited intelligence are also limited in their ability to care for themselves so that they need support from their families. From the results of the study conducted by researchers on June 25, 2018, on 30 respondents, who received support supported by the family of 21 respondents and who received less support as many as 9 respondents. while self-care ability, which is capable of 20 respondents who can self-care and 10 poor respondents in self-care. This study aims to determine the relationship of family support with the ability of self-care in children's Mental Retardation in Bulukumba 1 Public Middle School in 2018. The research method uses an analytical design with a "cross-sectional" approach. The population in this study is 42 people. The sample of this study as many as 30 respondents showed family support in the criteria supporting 21 respondents and those who did not support 9 respondents with the purposive sampling method. The results of the analysis of the relationship between family support with the ability of self-care in children's Mental Retardation in Bulukumba 1 Public Middle School in 2018, with Fisher's alternative chi-square statistical test, with a level of confidence (α = 0.05). Based on the test results obtained values ​​(p = 0,000) then Ho is rejected and Ha accepted. The conclusion of this study is, "The Relationship of Family Support with Self-Care Ability in Children Mental Retardation in Bulukumba 1 Public Middle School in 2018 It is suggested to families, especially parents to more support and guide children with mental retardation to achieve good self-care abilities.